Effect of dose of behavioral treatment for obesity on binge eating severity. (August 2016) - Ariel, Aviva H.; Perri, Michael G.
Abstract: Objectives: We evaluated the effects of three doses of a behavioral intervention for obesity (High dose = 24 sessions, Moderate = 16 sessions, Low = 8 sessions) compared with a nutrition education control group (Control) on binge eating. We also examined whether participants with clinically significant improvements in binge eating had better treatment adherence and weight-loss outcomes than those who did not experience clinically significant improvements in binge eating. Finally, we examined the relation of pretreatment binge eating severity to changes at six months. Methods: Participants included 572 adults (female = 78.7%; baseline mean ± SD: age = 52.7 ± 11.2 years, BMI = 36.4 ± 3.9 kg/m 2 ) who provided binge eating data at baseline. We evaluated binge eating severity (assessed via the Binge Eating Scale ) and weight status at baseline and six months, as well as treatment adherence over six months. Results: At six months, participants in the Moderate and High treatment conditions reported greater reductions in binge eating severity than participants in the Low and Control conditions, p s < .02. Participants who demonstrated improvements in binge eating severity reported greater dietary self-monitoring adherence and attained larger weight losses than those who did not experience clinically significant reductions, p s < .001. Pretreatment binge eating severity predicted less improvement in binge eating severity over six months and fewer days with dietary self-monitoring records completed, p s ≤ .002. Conclusion: A moderate or high dose of behavioral weight-loss treatment may be required to produce clinically significant reductions in binge eating severity in adults with obesity. Highlights: Examined effects of dose of behavioral treatment for obesity on binge eating Moderate or high doses were associated with greater reductions in binge eating. Binge eating improvements were associated with treatment adherence and weight loss.